Bonjour :)
Réponse en explications étape par étape :
On considère l'expression : " D = 4x(3 - x) - (3 - 2x)(3 + 2x) " :
- Questions :
1) Calculer D :
a) Pour " x = 2 " :
D = 4x(3 - x) - (3 - 2x)(3 + 2x)
D = 4 * 2 * (3 - 2) - (3 - 2 * 2)(3 + 2 * 2)
D = 8 * 1 - (3 - 4)(3 + 4)
D = 8 - (- 1) * 7
D = 8 + 7
D = 15
b) Pour " x = - 3 " :
D = 4x(3 - x) - (3 - 2x)(3 + 2x)
D = 4 * (- 3) * [3 - (- 3)] - [3 - 2 * (- 3)][3 + 2 * (- 3)]
D = - 12 * (3 + 3) - (3 + 6)(3 - 6)
D = - 12 * 6 - 9 * - 3
D = - 72 + 27
D = - 45
2) Montrer que " D = 12x - 9 " :
D = 4x(3 - x) - (3 - 2x)(3 + 2x)
D = (4x * 3) - (4x * x) - [(3)² - (2x)²]
D = 12x - 4x² - (9 - 4x²)
D = 12x - 4x² - 9 + 4x²
D = 12x - 9
Voilà